(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2023)
Background: Many stroke patients develop swallowing difficulty and require nasogastric feeding for the maintenance of nutrition. Objectives: The purpose of the present study was to evaluate the complications of nasogastric tube feeding practice on stroke patients. Methodology: This cross-sectional study was conducted from April 2014 to September 2014 in the Department of Medicine at Dhaka Medical College Hospital, Dhaka, Bangladesh. Adult patients aged between 18 to 70 years with stroke was enrolled in the study. The diagnosis of stroke was established by the clinical presentation and neuroimaging. Patients requiring nasogastric tube feeding was included in the study and were systematically examined for any complications related to use of nasogastric tube. Their caregivers were also thoroughly interviewed using a standard pre formed questionnaire regarding any complications as well. Results: Of the 100 patients studied, most common age group for stroke was 51 to 60 years (53.0%). Male to female ratio was 2.22:1. In this study population, 63.0% patients had ischaemic stroke; 26.0% had haemorrhagic stroke; 9.0% population had subarachnoid haemorrhage. The most common indication for NG feeding was difficulty in swallowing (39.0%). Other common indications were semi-consciousness (26%), unconsciousness (22.0%), inability to maintain feed (10.0%). Around 71.0% of the patients had complications from NG tube feeding. Out of them, 53.0% of the patients had nasal irritation, 40.0% patients developed aspiration pneumonia. 38.0% of the patients developed diarrhea, 53.0% had tube blockage. 43.0% of the patients had electrolyte imbalance and tube displacement, 18.0% of the patients were malnourished. Conclusion: In conclusion nasogastric tube feeding is associated with various complications which can increase the morbidities in stroke patients. Journal of National Institute of Neurosciences Bangladesh, July 2022;8(2):136-142